Factors that attract customers to bank with Social Islami Bank Limited (SIBL) - Bristy, Jannatul Ferdoshi (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2015.